2010
DOI: 10.1002/mde.1492
|View full text |Cite
|
Sign up to set email alerts
|

Endogeneity and the relationship between board structure and firm performance: a simultaneous equation analysis for the Athens Stock Exchange

Abstract: The main goal of this paper is to examine the relationship between the three most important characteristics of the board of directors with firm performance. More specifically, we investigate whether the independence of the board, the leadership structure and the board size, are exogenous determinants to the firm's performance, using a simultaneous equations framework. Our database is composed of firms quoted in the ASE, starting from 146 observations in 2000 and ending with 232 firms in 2006. The findings sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 48 publications
(72 reference statements)
2
21
0
Order By: Relevance
“…While some studies found a negative correlation between these variables (Agrawal and Knoeber, 1996;Bhagat and Black, 1999), others supported the idea of a positive correlation between the variables (Rosenstein and Wyatt, 1990;Dahya and McConnell, 2007). However, many studies also suggested that board independence has no statistically significant effect on the firm's financial performance (Hermalin and Weisbach, 1991;Drakos and Bekiris, 2010). Johnson et al (1996) concluded that relationships between board independence and performance might not exist.…”
Section: Board Of Directors and Firm Performancementioning
confidence: 84%
“…While some studies found a negative correlation between these variables (Agrawal and Knoeber, 1996;Bhagat and Black, 1999), others supported the idea of a positive correlation between the variables (Rosenstein and Wyatt, 1990;Dahya and McConnell, 2007). However, many studies also suggested that board independence has no statistically significant effect on the firm's financial performance (Hermalin and Weisbach, 1991;Drakos and Bekiris, 2010). Johnson et al (1996) concluded that relationships between board independence and performance might not exist.…”
Section: Board Of Directors and Firm Performancementioning
confidence: 84%
“…On the other hand, numerous researchers favour smaller boards and are of the view that large boards lead to non-cooperation and waste of time in decision making as they suffer from social loafing. Thus, their knowledge and skills remain unutilized (Dharmadasa et al, 2014;Drakos, & Bekiris, 2010;Jensen, 1993;Lin, 2011).…”
Section: Board Size and Firm Performancementioning
confidence: 99%
“…This approach also assists us in addressing issues of endogeneity in relation to board appointments and performance (Hermalin and Weisbach (2003) and Drakos and Bekiris (2010)). For example, as specified, NXXDs positively affect the appointing firm's performance.…”
Section: Dynamic Panel Data Robustness Analysismentioning
confidence: 99%